Domestic Violence from the Perspective of the Abused Women at Al-Wifaq Family House - Al-Karaki, Nisreen Mahmod Mohammad (Dirasat: Human and Social Sciences, 2026)
Objectives: The study aimed to identify demographic factors of abused women residing in Dar Al-Wefaq, as well as to know the extent of their exposure to violence in childhood, and to explore whether any family member practices violent behavior against children. Methodology: The study used descriptive approach, as study sample consisted of 18 abused women who frequent Dar Al-Wefaq Family. The study tool was also constructed through questionnaire that measures prevalence of violence within family and the extent to which abused women were exposed to violence in childhood, in addition to transmission of violence between family members. Results: The results showed that married women are more exposed to violence, increasing number of children in family associated with increased rates of domestic violence. Furthermore, abused women were working and educated, they were exposed to violence from their families during childhood and were exposed to it by their husbands in their new families. The most common type of violence was physical violence, followed by economic, psychological and emotional neglect. The study showed that all members of abused family were exposed to violence within family, the mother being most violent towards the children, followed by siblings, and most common types of violence practiced by the mother were neglect and psychological violence. Conclusion:It was found that violence is transmitted among members of society through learning, as abused women went through experiences of domestic violence from their families, and violence was transmitted to their new families.